Proton Magnetic Resonance Spectroscopy Lactate/N-Acetylaspartate Within 48 h Predicts Cell Death Following Varied Neuroprotective Interventions in a Piglet Model of Hypoxia–Ischemia With and Without Inflammation-Sensitization - Pang, Raymand; Martinello, Kathryn A.; Meehan, Christopher; Avdic-Belltheus, Adnan; Lingam, Ingran; Sokolska, Magda; Mutshiya, Tatenda; Bainbridge, Alan; Golay, Xavier; Robertson, Nicola J. (Frontiers in Neurology, 2020)
Despite therapeutic hypothermia, survivors of neonatal encephalopathy have high rates of adverse outcome. Early surrogate outcome measures are needed to speed up the translation of neuroprotection trials. Thalamic lactate/N-acetyl aspartate (Lac/NAA) peak area ratio acquired with proton (1H) magnetic resonance spectroscopy accurately predicts 2-year neurodevelopmental outcome. We assessed the relationship between MR biomarkers acquired at 24-48h following injury with cell death and neuroinflammation in a piglet model following various neuroprotective interventions. 67 piglets with either hypoxia-ischemia, hypoxia alone or LPS sensitization were included and neuroprotective interventions included therapeutic hypothermia, melatonin and magnesium. MRS and diffusion-weighted imaging were acquired at 24h and 48h. At 48h, experiments were terminated and immunohistochemistry assessed. There was a correlation between Lac/NAA and overall cell death (TUNEL)(mean Lac/NAA BGT voxel r=0.722, WM voxel r=0.784, p<0.01) and microglial activation (Iba1)(BGT r=-0.786, WM r=-0.632, p<0.01). Correlation with marker of caspase dependent apoptosis (CC3) was lower (BGT r=-0.636, WM r=-0.495 (p<0.01). Relation between DWI and TUNEL was less robust (Mean Diffusivity BGT r=-0.615, Fractional Anisotropy BGT r=0.523). Overall, Lac/NAA correlated best with cell death and microglial activation. These data align with clinical studies demonstrating Lac/NAA superiority as an outcome predictor in NE and supports its use in pre-clinical and clinical neuroprotection studies.